2013
DOI: 10.1073/pnas.1216145110
|View full text |Cite
|
Sign up to set email alerts
|

Early quality assessment lessens pheromone specificity in a moth

Abstract: Pheromone orientation in moths is an exemplar of olfactory acuity. To avoid heterospecific mating, males respond to femaleproduced blends with high specificity and temporal resolution. A finely tuned sensory to projection neuron network secures specificity, and this network is thought to assess pheromone quality continually during orientation. We tested whether male moths do indeed evaluate each pheromone encounter and surprisingly found that male European corn borer moths instead generalize across successive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…; Kárpáti et al . ). The difference in distance range might reflect a difference in resolution between the olfactory senses of moths and beetles (Andersson et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Kárpáti et al . ). The difference in distance range might reflect a difference in resolution between the olfactory senses of moths and beetles (Andersson et al .…”
Section: Discussionmentioning
confidence: 97%
“…This approach has been justified by the observation that E-strain males may exhibit earlier signs of attention to the Z lure and the opposite applies to Z-strain males; such signs are unreliable predictors of the final outcome (38). However, recent studies have shown that early responses by Z-strain males can lock them in to subsequent behaviors that are maintained even if the pheromone lure is experimentally switched from Z to E while the moth is in midflight (40). Thus, variation in the early responses also may be a relevant indicator of genetic differences between the Z and E strains.…”
Section: Discussionmentioning
confidence: 99%
“…In moths, behavioral responses of males to sex pheromones have been well investigated [1]. The pheromone cocktail emitted by females usually contains several compounds, the ratio of which is crucial for male attraction [2], [3]. Male attraction to sex pheromones can, however, be augmented by presenting the pheromone against a relevant leaf volatile blend emitted by a suitable larval host plant [4], [5].…”
Section: Introductionmentioning
confidence: 99%